Differential Expression of Metallothioneins and Slc Family Genes in Accommodation and Subclinical Antibody Mediated Rejection. (July 2018) - Hruba, Petra; Krejcik, Zdenek; Stranecky, Viktor; Gueler, Faikah; Gwinner, Wilfried; Parikova, Alena; Slatinska, Janka; Wohlfahrtova, Mariana; Striz, Ilja; Fronek, Jiri; Maluskova, Jana; Honsova, Eva; et al.
Abstract : Introduction: Accommodation in ABOi kidney transplantation has been defined as persistence of hemagglutinins on endothelial cells (C4d positivity in protocol biopsies) without deleterious effect on graft dysfunction in long-term. In subclinical antibody mediated rejection, C4d deposition in protocol biopsies caused by donor specific anti-HLA antibodies binding to endothelial cells substantially influence graft function. With the aim to elucidate the mechanism of accommodation, molecular processes involved in those two different ways of complement activation were studied. Methods: Transcriptome of 3-months C4d positive protocol biopsies in ABOi patients (n=11) and in HLAi cohort with positive donor specific antibodies (n=7) was assessed using Illumina Human HT-12 v4 Expression BeadChips. Moreover, transcriptome of both groups was compared to C4d negative protocol biopsies with normal histological findings (n=8, controls). ABOi and HLAi groups did not differ in Banff scores. Biopsies of controls had besides C4d negativity lower cv score. Differentially expressed genes were defined as those with fold change ≥2 and p<0.05. The enrichment of deregulated genes in biological processes was analyzed using DAVID database and results were validated using real-time qPCR at the independent cohort (n=24). Results: The hierarchical clustering of gene expression profiles of samples from HLAi, ABOi and control groups did not result in formation of 3 main clusters. Instead 4 clusters were formed: 2 clusters included exclusively ABOi and control samples and 2 clusters included samples from all groups. This suggests no major clear difference among transcriptome profiles of all 3 groups. GO terms with the highest fold enrichment for deregulated genes between ABOi and HLAi group were represented by cadmium ion binding (p=0.0016), apical plasma membrane (p=0.008) and anion transmembrane transporter activity (p=0.032). Majority of deregulated genes between both groups belongs to metallothioneins (MT) and solute carrier family (Slc) genes. The decreased expression of 5 Slc family genes ( SLC4A1; SLC4A9; SLC17A3; SLC12A3; SLC30A2 and 3 metallothioneins of class1 ( MT1F, MT1G and MT1X ) in ABOi compared to HLAi group was verified by RT-qPCR. When transcriptomes of HLAi or ABOi were compared to C4d negative controls, in both HLAi and ABOi group genes including in GO term mitochondrion (p=0.021 and 0.0075, respectively) were upregulated. In controls compared to HLAi group were upregulated genes from GO terms: extracellular matrix (p=2.3 E-06), proteinaceous extracellular matrix (p= 4.30E-06) and cell adhesion (p= 0.0012). Conclusion: Contrary to hemagglutinins, anti-HLA antibodies activate both MTs of class 1 and Slc genes. Dysregulation of MTs and distinct Slc family genes might be involved in ABOi accommodation. Supported by Ministry of Health of the Czech Republic (MZO 00023001) and by the Grant Agency of the Ministry of Health of the Czech Republic (No. 15-26865A).